Analisis Faktor-faktor yang Memengaruhi Volume Ekspor Kopi Indonesia ke Mesir Tahun 2001-2022 - Utami, Sri; Supriadi, Apip; Sukarso, Aso (WELFARE Jurnal Ilmu Ekonomi, 2024)
This study aims to analyze the effect of domestic coffee production, Egyptian GDP per capita, and exchange rates on the volume of Indonesian coffee exports to Egypt in 2001-2022. This research method used in this study is a quantitative approach. This study uses annual data with a time span of 2001-2022. The data used in this study are secondary (time series) data sourced from the Central Bureau of Statistics, International Coffee Organization, and World Bank. The analytical method used is multiple linear regression. The results showed that partially domestic coffee production, Egyptian GDP per capita, and exchange rate had a positive and significant effect on the volume of Indonesian coffee exports to Egypt in 2001-2022. Jointly, domestic coffee production, Egyptian GDP per capita, and exchange rate have a significant effect on the volume of Indonesian coffee exports to Egypt in 2001-2022. Based on elasticity analysis, the volume of Indonesian coffee exports to Egypt proved to be elastic to domestic coffee production and exchange rate, but inelastic to Egypt’s GDp per capita.Penelitian ini bertujuan untuk menganalisis pengaruh produksi kopi domestik, GDP per kapita Mesir, dan nilai tukar terhadap volume ekspor kopi Indonesia ke Mesir tahun 2001-2022. Metode penelitian yang digunakan dalam penelitian ini yaitu pendekatan kuantitatif. Penelitian ini menggunakan data tahunan dengan rentang waktu 2001-2022. Data yang digunakan dalam penelitian ini adalah data sekunder runtun waktu (times series) yang bersumber dari Badan Pusat Statistik Indonesia, Internasional Coffee Organization, dan World Bank. Metode analisis yang digunakan adalah regresi linear berganda. Hasil penelitian menunjukkan bahwa secara parsial produksi kopi domestik, GDP per kapita Mesir, dan nilai tukar berpengaruh positif dan signifikan terhadap volume ekspor kopi Indonesia ke Mesir tahun 2001-2022. Secara bersama-sama produksi kopi domestik, GDP per kapita Mesir, dan nilai tukar berpengaruh signifikan terhadap volume ekspor kopi Indonesia ke Mesir tahun 2001-2022. Berdasarkan analisis elastisitas, volume ekspor kopi Indonesia ke Mesir terbukti elastis terhadap produksi kopi domestik dan nilai tukar, namun inelastis terhadap GDP per kapita Mesir.